Investigation of a Biodegradable Injectable In Situ Gelling Implantable System of Rivastigmine Tartrate - Koland, Marina (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Injectable in situ gelling solutions are novel implantable systems that combine the advantages of a prolonged release subdermal implant and the convenience of administration of an aqueous solution. Objectives: The aim of the present investigation was to formulate and evaluate a thermo-reversible injectable in situ gelling system of rivastigmine tartrate. Methods: Injectable in situ gelling solutions loaded with rivastigmine were formulated using the thermosensitive polymers: Pluronic F127 and Pluronic F68. The thermo-reversible gelling solutions were evaluated for gelation temperature, gel strength, syringeability and injectability, drug content, in vitro drug release studies, and ex vivo studies using extensor digitorum muscle of Gallus gallus domesticus. Results: Gelation temperature and gel strength increased with increasing concentrations of Pluronic F 68. All six formulations showed adequate ease on withdrawal and injection. The viscosity of formulations also increased with increase in the percentage of Pluronic F68 both in sol and gel form. An initial burst effect as a result of the immediate drug release from the sol form of the preparation before conversion to gel was observed from all formulations. Drug release was slower with an increase in the concentration of Pluronic F68. Ex vivo drug permeation studies for over 27 h exhibited slower release patterns from the selected formulations as compared to in vitro release. Conclusion: The developed formulations are capable of prolonging release of rivastigmine with the potential of achieving greater therapeutic success in Alzheimer patients compared to the conventional oral dosage forms.